2008
DOI: 10.1021/cb8001107
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Double- and Single-Stranded DNA Binding of E. coli Replicative DNA Polymerase III α Subunit

Abstract: The α subunit of the replicative DNA polymerase III of Escherichia coli is the active polymerase of the 10-subunit bacterial replicase. The C-terminal region of the α subunit is predicted to contain an oligonucleotide binding (OB-fold) domain. In a series of optical tweezers experiments, the α subunit is shown to have an affinity for both double- and single-stranded DNA, in distinct subdomains of the protein. The portion of the protein that binds to double-stranded DNA stabilizes the DNA helix, because protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 49 publications
4
47
0
Order By: Relevance
“…Because OB folds commonly bind to ssDNA, a proposal was made that the OB fold could be part of the sensing network 25, 26 . Consistent with this hypothesis, the ssDNA-binding portion of Pol III was localized to a C-terminal region of α that contains the OB-fold element 34 . A test of the importance of the OB-fold motif was made using a mutant in which three basic residues located in the β1-β2 loop were changed to serine 11 .…”
Section: Discussionmentioning
confidence: 53%
“…Because OB folds commonly bind to ssDNA, a proposal was made that the OB fold could be part of the sensing network 25, 26 . Consistent with this hypothesis, the ssDNA-binding portion of Pol III was localized to a C-terminal region of α that contains the OB-fold element 34 . A test of the importance of the OB-fold motif was made using a mutant in which three basic residues located in the β1-β2 loop were changed to serine 11 .…”
Section: Discussionmentioning
confidence: 53%
“…In contrast, ε by itself has been shown to be an ssDNA exonuclease, and the catalytic activity of ε is similar on ssDNA and mispaired primer termini. The ε subunit preferentially binds ssDNA, whereas α binds both ssDNA and dsDNA and prefers a primer‐template junction 30, 54. In addition, a recent NMR study showed that a primer destabilized due to mismatches increases the propensity of the mismatch to reach the ε subunit, enabling ε to correct for the mismatches in a passive manner 55.…”
Section: Discussionmentioning
confidence: 99%
“…The full-length crystal structure of Thermus aquaticus Pol III reveals similarities to E. coli Pol III [286], and a recent structure of the T. aquaticus α subunit shows the OB fold bound to DNA [290]. Single molecule DNA stretching experiments characterized the dsDNA and ssDNA binding activity of E. coli Pol III α, quantifying binding to both forms of DNA by distinct regions of the protein [291]. …”
Section: Proteins That Bind Both Double and Single-stranded Dnamentioning
confidence: 99%